Expression of Wnt/β-Catenin Signaling Pathway and Its Regulatory Role in Type I Collagen with TGF-β1 in Scleral Fibroblasts from an Experimentally Induced Myopia Guinea Pig Model - Min Li; Ying Yuan; Qingzhong Chen; Rao Me; Qing Gu; Yunjie Yu; Minjie Sheng; Bilian Ke (Journal of Ophthalmology)
Background. To investigate Wnt/β-catenin signaling pathway expression and its regulation of type I collagen by TGF-β1 in scleral fibroblasts from form-deprivation myopia (FDM) guinea pig model. Methods. Wnt isoforms were examined using genome microarrays. Scleral fibroblasts from FDM group and self-control (SC) group were cultured. Wnt isoforms, β-catenin, TGF-β1, and type I collagen expression levels were examined in the two groups with or without DKK-1 or TGF-β1 neutralizing antibody. Results. For genome microarrays, the expression of Wnt3 in FDM group was significantly greater as confirmed in retinal and scleral tissue. The expression of Wnt3 and β-catenin significantly increased in FDM group and decreased significantly with DKK-1. TGF-β1 expression level decreased significantly in FDM group and increased significantly with DKK-1. Along with morphological misalignment inside and outside cells, the amount of type I collagen decreased in FDM group. Furthermore, type I collagen increased and became regular in DKK-1 intervention group, whereas it decreased and rearranged more disorder in TGF-β1 neutralizing antibody intervention group. Conclusions. The activation of Wnt3/β-catenin signaling pathway was demonstrated in primary scleral fibroblasts in FDM. This pathway further reduced the expression of type I collagen by TGF-β1, which ultimately played a role in scleral remodeling during myopia development.